(untitled) (Studia Prawnicze / The Legal Studies, 2009)
Termin nomada stosuje się w języku aktów prawnych i nomenklaturze Rady Europy do osób wiodących historycznie uwarunkowany koczowniczy lub na wpół osiadły tryb życia. Do kategorii tej zalicza się, obok Romów, ludy mające wspólne z nimi korzenie bądź podobną obyczajowość. To ostatnie kryterium przesądza o przynależności romskiej, nawet jeśli, wbrew definicji nomady, konkretna osoba osiedliła się na stałe w jakimś miejscu. Odrębności rasowe, etniczne, językowe i kulturowe przesądzają o aktualności społecznej marginalizacji ludności romskiej. Większość Romów żyje w warunkach skrajnego ubóstwa, bez dostępu do podstawowych usług socjalnych. Zważywszy że społeczność romska liczy dziś w Europie 10 milionów osób, jest to ogromne wyzwanie dla organizacji zajmujących się ochroną praw człowieka. Sytuacja, w jakiej znajdują się Romowie zagraża społecznej spójności państw członkowskich Rady Europy. Organizacja stara się o jej poprawę, m.in. w zakresie prawa do mieszkania. Prawo do mieszkania występuje wyraźnie w Zrewidowanej Karcie Społecznej. W pierwotnej i zmienionej wersji Karta Społeczna gwarantuje szeroko pojmowaną opiekę rodzinie. Opieka ta implikuje pomoc w załatwianiu problemów mieszkaniowych. Konwencja Europejska chroni prywatność mieszkania, życia rodzinnego i korespondencji oraz jego własność. Konwencja o mniejszościach stanowi natomiast o pomocy takim grupom społecznym, jak Romowie we wszechstronnej socjalizacji. Istnieją także uchwały organów Rady Europy bezpośrednio odnoszące się do kwestii zabezpieczenia im mieszkania Wymienione akty prawne stanowią w niniejszym opracowaniu podstawę koncepcji odpowiedniego mieszkania dla Romów w systemie prawnym Rady Europy. The concept of adequate housing stems from the Covenant. The Council of Europe legal system adopted and adjusted that concept to its own needs and aims. The concept of adequate housing with regard to Roma may be found there in a number of legal acts, including Article 31 of the Revised Charter, Articles 16 of Revised Charter and the Social Charter, Article 8 of the European Convention together with its Article 1 of the Protocol No. 1, Article 5 of the Minority Convention referring to social development of minorities as well as in many other resolutions adopted by various bodies of the Organisation concerning the problem. The concept of adequate housing in the Covenant constitutes of such elements like: accessibility habituality availability of services, materials and infrastructure, location, cultural adequacy and legal security of tenure. These are key factors which are crucial to determinate the adequacy of the housing. Theconcept of adequate housing for Roma within the Council of Europe is interpreted as follows. There exists a total ban on segregation policy of this population in settlements and it is to be eradicated. Initiatives should be launched to promote tolerance and regular contacts between nomads and non-nomads communities. It is incumbent on states to enact anti-discrimination laws and to implement them effectively. Given exceptionally harsh nature of nomads housing conditions alternative accommodation should be provided as a matter of priority, especially to those of them who live in settlements which endanger life of the inhabitants or are hazardous to their health. Central and local authorities shall actively co-operate while implementing housing projects for nomads. They must imply all necessary and functional infrastructure. Nomads ought to have free choice of their housing lifestyle. Legal security of tenure implies that all nomads enjoys legal and factual protection against such threats like forced eviction and other harassment.